Hyb-Seq for Flowering Plant Systematics. (October 2019) - Dodsworth, Steven; Pokorny, Lisa; Johnson, Matthew G.; Kim, Jan T.; Maurin, Olivier; Wickett, Norman J.; Forest, Felix; Baker, William J.
Abstract : High-throughput DNA sequencing (HTS) presents great opportunities for plant systematics, yet genomic complexity needs to be reduced for HTS to be effectively applied. We highlight Hyb-Seq as a promising approach, especially in light of the recent development of probes enriching 353 low-copy nuclear genes from any flowering plant taxon.